Since composing inverse functions gets us back where we started, sin(arcsin x) = x. Taking the derivative of each side of this equation gives us cos(arcsin x) × (arcsin x)' = 1 therefore This is correct, but we're not done. cos(arcsin x) is messy, and we can simplify it. On the righthand side, we have (x)' = 1. On the lefthand side, we have an outside function sin(□) and an inside function arcsin x. We need to use the chain rule. The derivative of sin(□) is cos(□), therefore (sin(arcsin x))' = cos(arcsin x) × (arcsin x)'. The simplification is the part that relies on SOHCAHTOA and the Pythagorean theorem. arcsin x is an angle. Call that angle θ. Then θ = arcsin x means sin θ = x. Since , we know A triangle representing this equation would look something like this: Using the Pythagorean Theorem we can find the missing side of the triangle (in terms of x): We want to know cos(arcsin x) therefore we can simplify the equation If arcsin x = θ, then cos (arcsin x) = cos (θ). Looking at the triangle and using SOHCAHTOA, we see that Now we can finish the simplification.
